2005
DOI: 10.1097/01.don.0000145430.35906.fa
|View full text |Cite
|
Sign up to set email alerts
|

Buccal Bone Plate Thickness of the Asian People

Abstract: Distances from the apex to the buccal bone plate were measured on the computed tomography (CT) images of 1806 teeth from 66 patients, using an image analyzer program (Image-Pro Plus, Ver. 4.0, Media Cybernetics). In the mandible, the mean distance from the distal apex of the mandibular second molar to the buccal bone plate was the largest distance measured, at 8.51 mm, followed by distance from the mesial root to the buccal bone (7.34 mm). In the mandibular first molar, the mean distal and mesial bone thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
36
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 9 publications
4
36
0
1
Order By: Relevance
“…In daily clinical practice, there are some cases where the conventional intraoral radiography and/or panoramic radiography alone does not provide enough information on the pathologic conditions, anatomical forms and structures, and positional relationships. Computed tomography (CT) allows detailed three-dimensional (3D) observation of those forms and shapes, and its usefulness in endodontic therapy has been reported (2)(3)(4)(5)(6)(7)(8)(9). The conventional medical CT, however, exposes the patient to a dozens of times higher radiation dose than does intraoral radiography or panoramic radiography; and, therefore, its application may be limited in dentistry.…”
mentioning
confidence: 99%
“…In daily clinical practice, there are some cases where the conventional intraoral radiography and/or panoramic radiography alone does not provide enough information on the pathologic conditions, anatomical forms and structures, and positional relationships. Computed tomography (CT) allows detailed three-dimensional (3D) observation of those forms and shapes, and its usefulness in endodontic therapy has been reported (2)(3)(4)(5)(6)(7)(8)(9). The conventional medical CT, however, exposes the patient to a dozens of times higher radiation dose than does intraoral radiography or panoramic radiography; and, therefore, its application may be limited in dentistry.…”
mentioning
confidence: 99%
“…buccal plate thickness, proximity to anatomical structures such as the mandibular nerve or inoperable sites such as lingual surfaces of mandibular molars) or financial factors preclude conventional implant placement. Buccal plate thickness may preclude surgical endodontic treatment in mandibular molars and the palatal root of maxillary molars (2). Although post removal is frequently possible in the hands of a skilled clinician, occasionally posts or separated instrument removal may pose risks greater than the potential benefits as compared with other options including extraction (3).…”
mentioning
confidence: 99%
“…However, a lack of knowledge about the buccolingual thickness of the jaw bone due to image magnification and distortion can hinder (27). In Jin et al, these values were reported from 66 patients as 4.09 mm and 7.34 mm (28). In our study, we measured thicknesses at the first and second molar mesial roots as 4.58 mm and 6.93 mm, respectively.…”
Section: Discussionmentioning
confidence: 57%